GC-MS analysis and antibacterial activity of Aquilaria malaccensis leaf extract - Mohd Noor, Najihah; Hashim, Yumi Zuhanis Has-Yun; Mohammad Tormizi, Ummu Athiyah; Mohd Nasir, Asmak Muti;ah; Zainudin, Nur Umisha (2019)
Ethnopharmacological practices have shown significant evidences of agarwood material as having myriad of pharmacological activities including anticancer, antipyretic and antioxidant. The complexity and variability of the chemical constitution of the plant establishes the quality of the medicinal products. The present study was carried out to identify the phytochemical constituents of both derivatized and non-derivatized Aquilaria malaccensisleaf ethanolic extract (ALEX) and to study the anti-bacterial activity of ALEX extracted using Soxhlet extraction method. The metabolite profiling of bioactive compounds of ALEX samples were conducted using gas chromatography - mass spectrometry (GC-MS) coupled with the principal component analysis (PCA). The screening on the bacterial activity of the extract was determined by using modified Kirby Bauer disc diffusion method against leading bacterial pathogens: Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Vibrio Vulnificus.GC-MS analysis of ALEX reveals a total of 127 compounds from the derivatized sample and only 22 compounds in the non-derivatized sample. Several biological active compoundsthat werefound in ALEX samples include hexadecanoic acid, trimethyl ester, hexadecenoic acid, ethyl ester, 2(4H)- Benzofuranone, 5,6,7,7a-tetrahydro-4,4,7a- trimethyl-, trans-9-Octadecenoic acid, trimethylsilyl ester and 4-Isopropylphenol, trimethylsilyl ether. ALEX showed comparable anti-bacterial activity with zone of inhibition of 6.0 - 15.7 mmfor gram positive bacteria and 2.0 - 13.0 mm for gram negative bacteria against control which is Dimethyl sulfoxide (DMSO). Penicillin was used as positive controlexhibited strong zone of inhibition of 21.0 – 28.3 mm. The antibacterial activity results indicate that ALEXpossessed mild to stronginhibitory activities against the pathogenic bacteria due to presence of various phytochemical constituents which can be used as source of drugs to fight infections caused by susceptible bacteria.